Analisa Perpindahan Panas pada Dapur Pelebur Portable Berbahan Bakar Oli Bekas - Prabowo, Wahyu Triharto; Putri, Fenoria; Witjahjo, Soegeng (Universitas Pahlawan Tuanku Tambusai, 2025)
Aluminum smelting is a large-scale business or UMKM to produce household appliances or as a machining aid. However, the aluminum smelting industry still uses many conventional furnaces that cannot be carried anywhere. Seeing this condition so that the aluminum smelting industry does not have difficulty in storing the melting furnace. This study was conducted to change the knowledge of heat and find the efficiency of portable melting furnaces using used oil. By varying 2 variables, namely the pressure setting of the wind speed from the blower of 7.61m / s, 7.76m / s, 7.92m / s and the oil tap discharge of 0.002 l / s, 0.012 l / s, 0.013 l / s as fuel for the portable melting furnace. And from 9 tests with different variations have obtained efficient results. Using a blower wind speed of 7.92 m/s and an oil discharge of 0.013 l/s for the melting time, which only takes 13 minutes, using 0.3 liters of oil as fuel and producing heat in the melting furnace of 7,022.0647 w/m℃ in one melting. Overall, increasing the blower speed and large oil discharge can increase the efficiency of the melting process by reducing the melting time and oil consumption, although the effect on temperature does not show a consistent pattern.